2008
DOI: 10.1080/02687030802025984
|View full text |Cite
|
Sign up to set email alerts
|

Parental influences on earliest memories

Abstract: Recently, independent lines of research have indirectly supported the notion that social variables, especially parent-child relationships, have a significant impact on adults' memories of their early life. In order to directly assess this Italian students were asked to recall as many memories involving parents as they could from before the age of 6 in a 3-minute timed recall task (i.e., memory fluency). They also filled out assessments about parental involvement in their lives as well as the quality of their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 39 publications
4
33
2
Order By: Relevance
“…Furthermore, those individuals that have parents who are more supportive and involved with their children have relatively more positive memory reports about parents than do those individuals with more conflictual and less positive parent-child relationships [7,34,44]. However, these researchers assessed the overall emotional tone of short memory reports that had been gathered during a memory fluency task rather than assessing the number and emotional valence of specific emotion words in individuals' memory narratives about parents -which are considerably longer than the short reports elicited by a memory fluency task.…”
Section: Narratives -The Language Of Memoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, those individuals that have parents who are more supportive and involved with their children have relatively more positive memory reports about parents than do those individuals with more conflictual and less positive parent-child relationships [7,34,44]. However, these researchers assessed the overall emotional tone of short memory reports that had been gathered during a memory fluency task rather than assessing the number and emotional valence of specific emotion words in individuals' memory narratives about parents -which are considerably longer than the short reports elicited by a memory fluency task.…”
Section: Narratives -The Language Of Memoriesmentioning
confidence: 99%
“…'), whereas narratives describing repeated events or events that extended over days or weeks were classified as repeated event narratives (e.g.,: 'I remember the endless discussions between my parents during my high school years........' or ' Those wonderful evenings with my friends watching the stars during the summer before I began University......'). We followed the same scoring system as used in other research (e.g., Peterson et al, 2008;). …”
Section: Episodic Versus Repeated Eventsmentioning
confidence: 99%
“…In these investigations, reports of repeated events occurred frequently. Among children, Peterson et al (2009) Peterson et al (2008) reported that about half the reports of early childhood events consisted of accounts of repeated experiences.It is clear that, when allowed to do so, participants define their childhood memories as involving both unique and repeated experiences. But do the two types of memories serve the same function in autobiographical memory?…”
mentioning
confidence: 99%
“…In these investigations, reports of repeated events occurred frequently. Among children, Peterson et al (2009) Peterson et al (2008) reported that about half the reports of early childhood events consisted of accounts of repeated experiences.…”
mentioning
confidence: 99%
See 1 more Smart Citation